Russian thinkers - Berlin, Isaiah (London Penguin Books, 2013)
Few, if any, English-language critics have written as perceptively as Isaiah Berlin about Russian thought and culture. Russian Thinkers is his unique meditation on the impact that Russia's outstanding writers and philosophers had on its culture. In addition to Tolstoy's philosophy of history, which he addresses in his most famous essay, "The Hedgehog and the Fox," Berlin considers the social and political circumstances that produced such men as Herzen, Bakunin, Turgenev, Belinsky, and others of the Russian intelligentsia, who made up, as Berlin describes, "the largest single Russian contribution to social change in the world."
Includes index
Keywords: Russian thinkers